2008
DOI: 10.1186/1472-6882-8-48
|View full text |Cite
|
Sign up to set email alerts
|

Mapping patterns of complementary and alternative medicine use in cancer: An explorative cross-sectional study of individuals with reported positive "exceptional" experiences

Abstract: Background: While the use of complementary and alternative medicine (CAM) among cancer patients is common and widespread, levels of commitment to CAM vary. "Committed" CAM use is important to investigate, as it may be associated with elevated risks and benefits, and may affect use of biomedicallyoriented health care (BHC). Multiple methodological approaches were used to explore and map patterns of CAM use among individuals postulated to be committed users, voluntarily reporting exceptional experiences associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 19 publications
0
12
1
1
Order By: Relevance
“…As previous Nordic studies had shown a lack of consensus regarding the definition of CAM [3537], a questionnaire was developed to collect information about both the use of conventional as well as CAM treatments. The terms conventional or CAM treatment were not used in the questionnaire, to avoid response bias related to these labels.…”
Section: Methodsmentioning
confidence: 99%
“…As previous Nordic studies had shown a lack of consensus regarding the definition of CAM [3537], a questionnaire was developed to collect information about both the use of conventional as well as CAM treatments. The terms conventional or CAM treatment were not used in the questionnaire, to avoid response bias related to these labels.…”
Section: Methodsmentioning
confidence: 99%
“…The object(s) always receive the energy and responding into useful way, this process is known as biofield treatment or healing [15]. The National Center for Complementary and Alternative Medicine (NCCAM) considered this biofield treatment (therapy) in subcategory of energy therapies [16]. Mr. Trivedi's unique biofield energy is also known as biofield treatment (The Trivedi Effect → ).…”
Section: Insights In Analytical Electrochemistrymentioning
confidence: 99%
“…The manifest content analysis pertained to what both the healthcare professionals and the patients expressed; whereas, the latent content analysis pertained to the meaning of what they stated. Examples of related research are Granerud and Severinsson, 20 Høye and Severinsson, 21 Nystedt et al 22 The second manner analyzes manifest content, exemplified by Hök et al 23 They identified, coded and sorted into categories without meaning analysis. The third manner analyzes latent content, exemplified by Gustafsson et al 24 They explored older people's body experiences, developing meaning units, condensed meaning units, and themes, without explicit categorization.…”
Section: Data Analysis and Conceptual Developmentmentioning
confidence: 99%